Skin in the game in ABS transactions: A critical review of policy options - Christian Wilde; Jan Pieter Krahnen (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
This paper finds the current regulation of ABS in Europe and the US to be severely flawed with respect to its key intention: the imposition of a strict loss retention requirement. While nominal retention is always 5%, the true level of loss retention varies dramatically across available retention options. We propose a new risk retention metric RM measuring the level of an issuer's skin-in-the-game and propose making disclosure of the RM-number compulsory for all ABS transactions.
Keywords: G2; 330